The Influence of Online Customer Reviews and Online Customer Ratings on Purchase Decisions with Trust as the Intervening Variable - Nurhaliza, Nina; Yusup, Muhammad; Sanurdi, Sanurdi (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Along with the advancement of time, technology, and information in the world, especially the internet, have experienced rapid development. Various buying and selling transactions that previously could only be done face-to-face can now be easily accessed using smartphones. Online customer review and online customer rating features can be said to be one of the strategies found in marketplace applications, one of which is the Shopee marketplace. These features can certainly influence consumer purchasing decisions. Online customer reviews and ratings are features that consumers can use to obtain product-related information when shopping online. This study aims to analyze the influence of online customer reviews and online customer ratings on purchase decisions with trust as the mediator on the Shopee marketplace. The population in this study is millennial Muslim consumers who use the Shopee marketplace in Mataram City. Sampling was done using purposive sampling technique, with 100 respondents. The analysis technique used is SEM-PLS with Smart PLS 3 software. The results of this study found that there is no direct influence of online customer reviews and online customer ratings on purchase decisions. Only trust directly influences purchase decisions. Online customer reviews and online customer ratings directly influence trust. Meanwhile, online customer reviews and online customer ratings indirectly influence purchase decisions through trust.